Radość uzdrowienia i powrotu. O narracyjnych możliwościach wyrazu szczęśliwości, jej braku oraz radości (tłum. D. Chabrajska) - POTKAY, Adam (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
This essay has three parts, corresponding to the three concepts announced in its title: happiness, joy, and unhappiness. “Happiness” does not refer only to a feeling or subjective state, but designates as well an evaluation of a life or the narrative of a life. Accordingly, in representing the lives of fictional characters, novelists invite their readers to assess both what happy or flourishing lives might be, and the narrative routes, variously composed of circumstances and choices, by which such lives might be attained. Joy, as distinct from happiness, is an episodic or dispositional element in an individual’s emotional life, and as such not subject to public evaluation in quite the same way as happiness is. And yet joy, which is arguably with desire and sorrow one of the three fundamental emotions of narrative, can nonetheless be subjected to ethical discipline: the novelist can, and often does, prompt her reader to feel joy and grief at the right things. Finally, this article’s third section concerns the narrative importance of unhappiness in the novel, especially the Continental novel. An earlier version of this essay was published as “Narrative Possibilities of Happiness, Unhappiness, and Joy” in Social Research: An International Quarterly of the Social Sciences, volume 77, number 2, Summer 2010. Used with permission of Social Research, www.socres.org.